Cultural Threads: ‘Kalembo Ade’ and its Islamic Roots in Bima - Muhammad al-Anhar al-Islami; Anggar Putra; Pajarudin Pajarudin (UIN Syarif Hidayatullah Jakarta, 2024)
The use of Kalembo Ade as a local identity leaves a concern for its speakers to interpret this expression in a literal sense. This research aims to explore a deep understanding of the local idiom Kalembo Ade both literally and in the context of its use and explore the values implied by the use of the idiom Kalembo Ade in the lives of its origin. By exploring its meaning, this article synthesizes further the significance of the use of the Kalembo Ade in the terms of spiritual values of Islamic roots in Bima. This research uses a qualitative approach based on cultural memory studies by conducting in-depth interviews, enumerating literal meanings through text analysis, and observing the use of Kalembo Ade. The data sources in this research are Bima language speakers (origin), consisting of those from the ethnic of Bima in West Nusa Tenggara, as well as several articles related to the term Kalembo Ade. The research results show that there are several contexts for the use of the term Kalembo Ade in everyday life, including as an expression of gratitude, apology, condolences, and accepting or rejecting a consensus. Some of these contexts were also found to be attached to spiritual values maintained by society regarding manners of behavior and speech (attitude) according to Islamic roots. This research also shows that there are some intentions to preserve local cultural values through the widespread use of Kalembo Ade by the local community